GAME BALINESE FRUIT SHOOTER BERBASIS VIRTUAL REALITY SEBAGAI MEDIA PEMBELAJARAN DI TAMAN KANAK-KANAK - Pranata, Made Aditya (EDUTECH, 2017)
Abstract. Local Balinese fruits competed between imported fruit which existence was not uncommon and some local Balinese fruits that were once very popular in the community, and now that was rarely founded. The present generation is more familiar with various imported fruits than local fruits, especially in Bali (Rai, 2016). Based on these problems required a media used to introduce local Balinese fruit, one of which is imstructional media. The Activities are grouping local Balinese fruit by color by shooting. That activities are conducting to motivate the interest of learning, to increase insights related to local Balinese fruit, to introduce local Balinese fruit to kindergarten children, and to give an overview of the form of local Balinese fruit. Development of Balinese Fruit Shooter game based on Virtual Reality as instructional media in Ceria Asih of Kindergarten Singaraja using ADDIE model. The final result is a Virtual Reality based Balinese Fruit Shooter game about shooting local Balinese fruits by color as an introduction to local Balinese fruit for early childhood that can be played through a computer with HTC VIVE headsets. Results for field trials involving 10 children of Ceria Asih Kindergarten Singaraja reached 92.2% with very appropriate criteria. This application can be used as a media to introduce the local fruit of Bali in learning in kindergarten with sub themes of fruits.Abstrak. Buah lokal Bali bersaing antara buah impor yang keberadaannya tidak jarang ditemukan dan beberapa buah lokal Bali yang dulu sangat populer di masyarakat, saat ini sudah mulai jarang ditemukan. Generasi sekarang lebih mengenal berbagai buah impor daripada buah lokal khususnya di Bali (Rai, 2016). Berdasarkan permasalahan tersebut diperlukan suatu media yang digunakan untuk memperkenalkan buah lokal Bali, salah satunya adalah media pemebelajaran. Kegiatan yang dilakukan adalah mengelompokan buah lokal Bali berdasarkan warna dengan cara menembak. Kegiatan tersebut dilakukan guna memotivasi minat belajar, menambah wawasan terkait dengan buah lokal Bali, memperkenalkan buah lokal Bali kepada anak-anak TK, serta memberikan gambaran bentuk dari buah lokal Bali. Pengembangan game Balinese Fruit Shooter berbasis Virtual Reality sebagai media pembelajaran di TK Ceria Asih Singaraja menggunakan model ADDIE. Hasil akhir berupa game Balinese Fruit Shooter berbasis Virtual Reality tentang menembak buah lokal Bali berdasarkan warna sebagai pengenalan buah lokal Bali untuk anak usia dini yang dapat dimainkan melalui komputer dengan headset HTC VIVE. Hasil untuk uji lapangan yang melibatkan 10 anak-anakTK Ceria Asih Singaraja mencapai nilai 92,2% dengan kriteria sangat sesuai. Aplikasi ini dapat dijadikan sebagai media untuk memperkenalkan buah lokal Bali dalam pembelajaran di TK dengan sub tema buah-buahan.